La aparición de Thyrinteina arnobia (Stoll) (Lepidoptera: Geometridae) de Eucalyptus y su depredación por Zelus armillatus (Lepeletier y Serville) (Reduviidae: Harpactorinae) - Barreto, Marliton Rocha; Mojena, Pastor Amador (EntomoBrasilis, 2014)
Los lepidópteros más importantes para el cultivo de los eucaliptos son los defoliadores y en Brasil, algunas especies se encuentran desde el estado de Amazona hasta Rio Grande del Sur. Thyrinteina arnobia arnobia (Stoll) (Lepidóptera: Geometridae) se cita como el lepidóptero defoliador más importante en Brasil y algunas especies depredadoras de la familia Reduviidae están asociados con diversos cultivos forestales. En este estudio se registra la ocurrencia de Zelus armillatus (Lepeletier & Serville) depredando a T. arnobia en plantaciones de eucaliptus en la ciudad de Sorriso, estado de Mato Grosso, Brasil. Registration of Thyrinteina arnobia arnobia (Stoll) (Lepidoptera: Geometridae) in Eucalyptus sp. (Myrtaceae) in Sorriso, Mato Grosso and its predation by Zelus armillatus (Lepeletier & Serville) (Hemiptera: Reduviidae: Harpactorinae) Abstract. The most important lepidopterans for eucalyptus crop are called defoliators. In Brazil, some species occur from the Amazônia to Rio Grande do Sul State and Thyrinteina arnobia arnobia (Stoll) (Lepidoptera: Geometridae) is cited as the most important lepidopteran defoliator in Brazil and some predatory species of the family Reduviidae are associated with various forest crops. Thus, this study recorded the ocorrence of Zelus armillatus (Lepeletier & Serville) preying T. arnobia in eucaliptus crop in Sorriso city, Mato Grosso state, Brazil.